2002
DOI: 10.1007/s101470200051
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 5-FU sensitivity using human colorectal cancer specimens: comparison of tumor dihydropyrimidine dehydrogenase and orotate phosphoribosyl transferase activities with in vitro chemosensitivity to 5-FU

Abstract: DPD and OPRT activities within cancer cells may predict positive sensitivity to 5-FU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 5 publications
7
42
0
1
Order By: Relevance
“…Previous clinical studies also revealed the positive expression and activity of OPRT to be associated with the responsiveness to 5-FU in a variety of human cancers, including colorectal cancers (Isshi et al, 2002;Fujii et al, 2003;Ichikawa et al, 2003a;Matsuyama et al, 2006) and bladder carcinomas (Mizutani et al, 2004). However, these studies were performed using relatively small number of patients, and then were evaluated by biochemical assays for OPRT enzyme activity or reverse transcriptional PCR (RT -PCR) assays for OPRT gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous clinical studies also revealed the positive expression and activity of OPRT to be associated with the responsiveness to 5-FU in a variety of human cancers, including colorectal cancers (Isshi et al, 2002;Fujii et al, 2003;Ichikawa et al, 2003a;Matsuyama et al, 2006) and bladder carcinomas (Mizutani et al, 2004). However, these studies were performed using relatively small number of patients, and then were evaluated by biochemical assays for OPRT enzyme activity or reverse transcriptional PCR (RT -PCR) assays for OPRT gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have reported their sensitivity to be associated with the target molecule TS (Rustum et al, 1997), fluoropyrimidinemetabolising enzymes such as orotate phosphoribosyltransferase (OPRT) (Peters et al, 1986), and the 5-FU-catabolitic enzyme such as dihydropyrimidine dehydrogenase (DPD) (Beck et al, 1994). However, there were only a few clinical studies on the simultaneous evaluations of these biomarkers to evaluate 5-FU sensitivity (Isshi et al, 2002;Fujii et al, 2003;Ichikawa et al, 2003a).…”
mentioning
confidence: 99%
“…High OPRT activity was associated with good in vitro sensitivity to 5-FU, measured by Collagen Gel Droplet Embedded Culture Drug Sensitivity test, Fluoresceine Diacetate Assay or Histoculture Drug Response Assay, in human colorectal cancer tissues. 68,69 Furthermore, in 37 patients treated with oral tegafur-uracil for disseminated colorectal cancer, responding tumours had higher expressions of OPRT than nonresponding tumours. 70 In the same study, there was no difference in UP mRNA between responding and nonresponding tumours.…”
Section: -Fluorouracilmentioning
confidence: 99%
“…To find such gene panels, far more studies are needed. Looking at current data, a combination of the expression of DPD, TS, TP and OPRT, all four crucial enzymes in the metabolism of 5-FU, at least appears to be a promising approach in colorectal cancer [68][69][70][184][185][186] (Table 5). …”
Section: Impact Of Current Data On Clinical Practicementioning
confidence: 99%
“…Several 5-FU-related metabolic enzymes are thought to correlate with the sensitivity to 5-FU (4)(5)(6)(7)(8)(9)(10). Two main modes of action have been proposed for 5-FU through its active metabolites, 5-fluoro-2'deoxyuridine-5'-monophosphate (FdUMP) and 5-fluoro-uridine-5'-triphosphate (FUTP) (10).…”
Section: Introductionmentioning
confidence: 99%